Royal Family’s Cancer Diagnoses Oﬀer A Supreme Authority to Rectify Cancer Therapies to Save Cancer Patients (London Journal of Medical and Health Research, 2024)
NA
Keywords: enzymes.; Burns; hypertrophic scars; skin grafts; collagenase; recombinant.; Total ischemic time; Primary PCI (pPCI); prognostic implications.; Chemotherapy; Cancer therapy; differentiation therapy; immunotherapy; CDA; CSCs; DIs; DHIs; PSCs; Wound healing.